Asymmetric Synthesis of 2‐Thiocyanato‐2‐(1‐aminoalkyl)‐substituted 1‐Tetralones and 1‐Indanones with Tetrasubstituted Carbon Stereogenic Centers via Cooperative Cation‐Binding Catalysis. Issue 11 (28th April 2017) - Yu, Lei; Wu, Xiaoyan; Kim, Mun Jong; Vaithiyanathan, Venkataramasubramanian; Liu, Yidong; Tan, Yu; Qin, WenLing; Song, Choong Eui; Yan, Hailong
Abstract: In this study, the concept of cooperative cation‐binding catalysis was applied for direct generation of two contiguous trisubstituted and tetrasubstituted stereogenic centers. Using the readily accessible chiral oligoethylene glycol (oligoEG) as a cation‐binding catalyst, asymmetric Mannich reactions of α‐thiocyanato cyclic ketones as Mannich donors were performed with α‐amidosulfones as the bench‐stable imine precursors in the presence of potassium fluoride as the base, affording 2‐thiocyanato‐2‐(1‐aminoalkyl)‐substituted 1‐tetralones and 1‐indanones possessing fully substituted C–SCN centers. The salient features of this process include (i) a transition metal‐free and operationally simple procedure, (ii) direct use of α‐amidosulfones as bench‐stable precursors of sensitive imines, (iii) direct enolization of racemic cyclic α‐thiocyanato ketones and (iv) excellent stereoselectivity with up to 99% ee and >20:1 diastereoselectivity ( anti:syn ). This protocol is easily scalable and provides a new approach for the syntheses of some biologically relevant products possessing fully substituted C–SCN centers. Abstract :